Comparison of Different Tidal Volumes for Ventilation in Patients with an Acute Traumatic Cervical Spine Injury - Sengupta, Deep; Bindra, Ashish; Kapoor, Indu; Mathur, Purva; Gupta, Deepak; Khan, Maroof (Neurology India, 2022)
Background: There is scant literature comparing high tidal volume ventilation (HTV) over low tidal volume (LTV) ventilation in acute traumatic cervical spinal cord injury (CSCI). Objective: The aim of this prospective randomized controlled parallel-group, single-blinded study was to compare the effect of two different tidal volumes (12-15 mL/kg and 6-8 mL/kg) in CSCI on days to achieve ventilator-free breathing (VFB), PaO2/FIO2 ratio, the incidence of complications, requirement of vasopressor drugs, total duration of hospital stay, and mortality. Materials and Methods: We enrolled patients with acute high traumatic CSCI admitted to the neurotrauma intensive care unit within 24 h of injury, requiring mechanical ventilation. Participants were randomized to receive either HTV, 12-15 mL/kg (group H) or LTV, 6-8 mL/kg (group L) tidal volume ventilation. Results and Conclusions: A total of 56 patients, 28 in each group were analyzed. Patient demographics and injury severity were comparable between the groups. VFB was achieved in 23 and 19 patients in groups H and L, respectively. The median number of days required to achieve VFB was 3 (2, 56) and 8 (2, 50) days, P = 0.33; PaO2: FIO2 ratio was 364.0 ± 64 and 321.0 ± 67.0, P = 0.01; the incidence of atelectasis was 25% and 46%, P = 0.16, respectively, in group H and group L. The hemodynamic parameters and the vasopressor requirement were comparable in both groups. There was no barotrauma. The duration of hospital stay (P = 0.2) and mortality (P = 0.2) was comparable in both groups. There was no significant difference in days to achieve ventilator-free breathing with HTV (12-15 mL/kg) ventilation compared to LTV (6-8 mL/kg) ventilation in acute CSCI. The PaO2:FiO2 ratio was higher with the use of 12-15 mL/kg. No difference in mortality and duration of hospital stay was seen in either group.